Effectivity of Inhibition of Oil Palm Empty Fruit Bunches Liquid Smoke Against Ganoderma boninense Fungus In Vitro - Riyani, Cica; Rahmawati, Linda; Majid, Zuliyan Agus NM (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2023)
Oil palm empty fruit bunches (OPEFB) can be processed into liquid smoke through pyrolysis. This study aimed to obtain the best concentration of unpurified liquid smoke from OPEFB in inhibiting the growth of the fungus of Ganoderma boninense. OPEFB samples were obtained from PT. Citra Putra Kebun Asri and G. boninense were collected from Muara Teweh Plantation. The study was conducted in 2 stages; Analysis of liquid smoke from pyrolysis using the GC-MS method at the Organic Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Gadjah Mada University; and testing the inhibition of liquid smoke on G. boninense in vitro at the Basic Plantation Cultivation Laboratory, Hasnur Polytechnic, and the Microbiology Laboratory of Plantation Products Processing Technology, Muara Teweh Polytechnic. This study was conducted in a completely randomized design with four treatments and six replications. The treatment was the difference in concentration of liquid smoke (1 ml/AC1, 2 ml/AC2, 3 ml/AC3, and control/AC0) in the planting medium, potato dextrose agar (PDA). The results showed that the average yield of unpurified liquid smoke from OPEFB was 34.5%, containing 49.28% acetic acid, 11.57% methyl alcohol, and 9.10% phenol. Application ? 2 ml liquid smoke in PDA completely inhibited G.boninense's growth in vitro, starting three days after application.